16S rrna gene characterization of the actinomycete- streptomyces tuirus, from the estuary region of Ariyankuppam, Puducherry- union territory, india. - PRIYA .M; ANANDARAJ .B (International Journal of Pharma and Bio Sciences, 2016)
The actinobacteria are found in aquatic and terrestrial habitats throughtout the world and are morphologically varied prokaryotes. Estuary Actinobacteria are relatively unexplored as potential source of novel species. In this study, the actinobacterial strains (n=50) isolated from the estuary region of Puducherry were screened for antimicrobial activity. Out of 50 strains PAS 9 (n=1) showing broad spectrum antibiotic producing nature was subjected to phylogenetic analyses (16S rRNA gene analysis), morphological and biochemical characterizations and was confirmed to be a novel rarely reported actinomycete- Streptomyces tuirus.